199k views
1 vote
Question 10 of 25

2 Points
If f(x) = 4x - 8 and g(x) = 5x + 6, find (+ 9)(x).
O A. (f+ 9)(x) = 4x - 3x+6
O B. (f+9)(x) = 9x - 2
O C. (f+9)(x) = -4* - 5x+ 2
O D. (f+9)() = 4x + 5x - 2
SUBMIT

User PinkyJie
by
5.4k points

2 Answers

4 votes

Answer:

B Combine all of your like terms

User Asukiaaa
by
5.5k points
6 votes

Answer:

Explanation:

If f(x) = 4x - 8 and g(x) = 5x + 6, find (f+ g)(x)

(f+ g)(x) = f(x) +g(x) = 4x-8 +5x+6

(f+ g)(x) =9x-2...answer : B

User Deepshikha Puri
by
6.4k points